Pengaruh Kualitas Tempat Tumbuh Terhadap Pertumbuhan Cemara Udang (Casuarina equisetifolia L.) Di Pantai Cemara Tuban: The Effect of Site Quality on Growth of Beach She-Oak (Casuarina Equisetifolia) on Cemara Beach, Tuban. - Istomo, Istomo; Susanti, Cindhy (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
Beach she-oak (Casuarina equisetifolia) is the one of the most commonly she-oak species that found and planted in coastal areas. Research was conducted to determine the growth of C. equisetifolia, environmental conditions, and the effect. Data were collected by making 10 circlular plots with a radius of 17,8 m with an area of 0,1 ha and 5 subplots in each plot. The data analysis used was understorey vegetation analysis, soil analysis, and multiple linear regression models of stepwise procedure. The results showed that the species of C. equisetifolia found amounted to 486 ind/ha at various growth stages and 10 species of understorey. The basal area is determined by stand density. The greater stand density, the greater the total growth. The best site quality based on average dominant height and age is found in plot 9. Factors that influence C. equisetifolia basal areas are soil pH, N-total, C-organic, temperature and humidity with of 80,4%.